Rural-urban differences in breast and colorectal cancer screening among US women, 2014-2019 - Nicholas Theodoropoulos; Hui Xie; Qian Wang; Chi Wen; Yannan Li (James Cook University, 2022)
Introduction: Prior research has revealed rural populations have lower rates of breast and colorectal cancer screening compared to their urban counterparts in the USA. An increasing number of rural hospitals have closed, with rural residents reporting skipping diagnosing imaging and preventative care due to a lack of access. Considering increasing rural hospital closures, this study investigated disparities in breast and colorectal cancer screening between urban and rural women in the USA. Methods: This cross-sectional study analyzed the Behavioral Risk Factor Surveillance System (BRFSS) data 2014-2019. Focusing on women aged 50-74 years, this study evaluated the prevalence of breast cancer and colorectal cancer (CRC) screening overall and by urban-rural location using multivariable logistic regressions. Results: During the study period, the adjusted prevalences of breast cancer screening were 80.0% and 77.1% (p<0.001) in urban and rural settings, respectively. The adjusted CRC screening prevalences were 72.8% and 68.4% (p<0.001) in urban and rural settings, respectively. By year, this study found that by 2019 there was no significant difference between urban and rural screening: 80.8% versus 79.6% in breast cancer and 78.9% versus 76.6% in CRC screening in urban and rural groups, respectively. Screening disparities existed between different racial groups. Conclusion: Breast cancer and CRC screening disparities between urban and rural women have narrowed; however, they continue to exist within these groups. The implementation of screening initiatives targeting underscreened rural regions and racial groups continues to be necessary.